Integrity and accountability in government homeland security and the Inspector General - Apaza, Carmen R. (Homeland security series, 2011)
The Inspector General (IG)'s mission is to expose fraud, waste and abuse as well as promoting efficiency in federal agencies. This book looks at the Inspector General for the Department of Homeland Security (DHS) which has proven to be of significant benefit to the US government.